Biomarkers of Oxidative Stress in Normal and Pre-eclamptic Women (KYAMC Journal, 2017)
Preeclampsia is a serious pregnancy complication. Little is known about which clinical risk factors are associated with the progression from normal to preeclampsia. Recent evidence suggests that the oxidative stress is one of the important factor associated with preeclampsia. High uric acid and MDA levels are indicative of oxidative stress. The purpose of this study was to evaluate the possible relationship between the biochemical markers (Uric acid & MDA) of oxidative stress in preeclamptic & normal pregnant women. In our study we investigated total number of 40 healthy pregnant and clinically diagnosed preeclamtic women. Among them 20 healthy (third trimester) normal pregnant women were taken as control group and another 20 clinically diagnosed PET women (at pre labour state) were taken as observational group. MDA and uric acid level were within normal range (2.63 ± 0.66 & 337.88 ± 16.52 ?mol/l ) respectively in normal pregnant women but significantly higher (3.74 ± 1.45 & 428.50 ± 23.65 ?mol/l ) in the group of preeclamptic women. This study review our current understanding of oxidative stress biomarkers ( Uric acid & MDA ) in preeclampsia and highlights that increased MDA and Uric acid levels are associated with preeclampsia.KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 406-408